Righteousness of God ability to live Christian holiness - Matijević, Dalia (2018)
The purpose of this article is to provide insight to what extent our conceptualization of the dikaiosyne theou shapes our way of understanding ourselves as Christians being the Body of Christ and living holy lives. Strongly influenced by the epistle to the Romans, we perceive holiness as being in right relation to God and righteousness being a practical consequence of this relationship. Holiness as the inner nature of God brings fruits of His righteousness, which is God’s saving activity. However, in the light of Christ and his sacrificial death and resurrection, relational, and eschatological perspectives of the dikaiosyne theou concept become crucial. This concept stands at the heart of Paul’s gospel and anticipates several layers of meaning, primarily God’s redeeming and saving activity, but also covenantal faithfulness and restorative justice brought by God and made available for all. Wider perspective is provided through the faithfulness of Jesus and his obedience to the Father in fulfilling salvific purposes. For us, it means a transformational and relational way of living in an eschatological perspective. Christian ethics are deeply grounded in the concept of dikaiosyne theou, and Christian conduct represents its practical and necessary expression. People living in genuine Christian community are marked by the righteousness of God expressed as agape and progressively transformed by the presence and involvement of his Holy Spirit. Such people involve themselves in a continuous process of discovering new opportunities to affirm God’s righteousness. Thus, the Christian community of faith needs to be inclusive in its nature.
Svrha ovoga članka jest pružiti uvid do koje mjere naše poimanje dikaiosyne theou oblikuje način na koji sami sebe vidimo kao kršćane koji predstavljaju Tijelo Kristovo i žive svetim životom. Pod utjecajem Poslanice Rimljanima, razumijemo svetost kao življenje u pravilnom odnosu s Bogom, a pravednost kao praktičnu posljedicu tog odnosa. Svetost kao unutarnja Božja priroda očituje se kao Božja pravednost, koja se pak ostvaruje kroz Božje spasiteljsko djelovanje. Međutim, u svjetlu Krista i njegove žrtvene smrti i uskrsnuća, relacijske i eshatološke dimenzije koncepta dikaiosyne theou se nameću kao presudne. Rečeni koncept stoji u samom središtu Pavlova evanđelja i pretpostavlja više slojeva značenja, prvenstveno Božje otkupiteljsko i spasiteljsko djelovanje, ali također i Božju zavjetnu vjernost te ponovno uspostavljenu pravednost koja je dostupna svakome. Šira perspektiva dikaiosyne theou se otvara kroz Isusovu odanost i poslušnost Ocu u ispunjavanju svrhe spasenja. Za nas to znači život koji podrazumijeva trajnu transformaciju na sliku Boga i samoostvarenje kroz odnos s Bogom i bližnjima u eshatološkoj perspektivi. Kršćanska je etika duboko ukorijenjena u konceptu dikaiosyne theou, a kršćanski način života predstavlja njegov nužni praktični izričaj. Ljudi koji žive u autentičnoj kršćanskoj zajednici obilježeni su Božjom pravednošću koja se izražava kao kolektivna agape, pri čemu bivaju progresivno preobražavani prisutnošću i djelovanjem Duga Svetoga. Takvi ljudi uranjaju u kontinuirani proces otkrivanja uvijek novih mogućnosti afirmiranja Božje pravednosti. Stoga kršćanska vjerska zajednica treba po svojoj naravi biti uključujuća.
Bilješke uz tekst.
Bibliografija: 21 jed.
Abstract ; Sažetak.
Keywords: Božja pravednost -- Spasenje -- Svetost -- Eshatologija -- Kršćanska zajednica -- Agape